The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2176/nmc.cr.2014-0204
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Traumatic Acute Subdural Hematoma in Adults: A Review

Abstract: Traumatic acute subdural hematoma (ASDH) is a major clinical entity in traumatic brain injury (TBI). It acts as a space occupying lesion to increase intracranial pressure, and is often complicated by co-existing lesions, and is modified by cerebral blood flow (CBF) changes, coagulopathy, and delayed hematomas. Because of its complicated pathophysiology, the mortality of ASDH is still remaining high. In this review article, its epidemiology, pathophyiology, surgical treatment, and salvage ability are described.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
1
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 62 publications
3
95
1
11
Order By: Relevance
“…Parenchymal herniation during the operation of patients with more significant injuries may prevent replacement of the bone flap. 3 The operating neurosurgeon may have been attempting to perform a craniotomy but due to technical reasons was unable to replace the bone. This is confounding by indication and occurs when variables associated with the outcome in the reference population, are also associated with the exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parenchymal herniation during the operation of patients with more significant injuries may prevent replacement of the bone flap. 3 The operating neurosurgeon may have been attempting to perform a craniotomy but due to technical reasons was unable to replace the bone. This is confounding by indication and occurs when variables associated with the outcome in the reference population, are also associated with the exposure.…”
Section: Discussionmentioning
confidence: 99%
“…1 Of those patients with a TBI, the frequency of acute subdural hemorrhage (ASDH) in patients is between 10–30%. 35 Furthermore, patients with ASDH often present with intracranial hypertension or neurologic dysfunction that requires emergent surgical decompression. 3 At the time of surgery, provided there is no extracranial herniation, it often remains unclear if the bone flap should be removed (decompressive craniectomy, DC) or replaced (craniotomy).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, some patients with a small hematoma and faint disturbance of consciousness on admission show a delayed, sudden increase in hematoma size, whereas other cases show no increase in hematoma size, resulting in good outcomes. Thus, the timing and decision of surgical intervention is an important issue for ASDH patients [5, 6, 14]. Correctly predicting the expansion of the hematoma is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic acute subdural hematoma (SDH) is a common condition confronting neurosurgeons, and it is reported that the percentage of acute SDH in patients admitted with a traumatic brain injury (TBI) is approximately 10–20%16,24). A previous study reported that approximately 60% of severe TBI patients have acute SDH to various extents.…”
Section: Introductionmentioning
confidence: 99%